Affective Touch Reduces Electrically Induced Itch Experience - Meijer, Larissa L.; Schielen, Zoë A.; van Ree, Kim Y.; Dijkerman, H. Chris (Frontiers in Medicine, 2021)
Introduction: Itch is a common symptom in dermatologic and other diseases and can have a severe impact on quality of life and mental health. As a proportion of patients with itch-symptoms is resistant to commonly used anti-histamine treatments, development of new treatments is desirable. Past research on pain, itch and affective touch (i.e. slow, gentle stroking of the skin activating c-tactile fibers) revealed an inhibitory relationship between affective touch and pain and between pain and itch. Given the overlap in neural processing between these three sensory submodalities, a possible interaction between affective touch and itch might be expected. This study investigated whether there is a relationship between itch and affective touch, and if so, whether affective touch inhibits itch. Methodology: Itch was electrically induced with the of use of electrodes that were placed at the ventral side of the wrist of 61 participants. A within-subject design was conducted with two conditions. An experimental -affective touch- condition (stroking the forearm with a soft brush at 3 cm/s) and a control -non-affective touch- condition (stroking the forearm with a soft brush at 18 cm/s). Touch was applied on the dorsal side of the forearm, the same arm as were the electrodes were placed. For each condition itch was induced for 20 minutes, with every 2 minutes a VAS-scale measurement of the level of experienced itch. Results: Both types of touch reduced the experienced itch compared to baseline (p < .01, partial η^2 = .67). However, affective touch had an additional significant relieving effect compared to non-affective touch (p =.03, partial η^2= .08 ) . Compared to the control condition, affective touch had a relieving effect on itch. The alleviation of itch started after 2 minutes of stroking and continued to increase up till 6 minutes, where after the relieving effect stabilized but still persisted. Conclusion: This finding suggest that affective touch, as with acute pain, has a relieving effect on mechanically electrically induced itch.